HLA–DPB1 as a Risk Factor for Relapse in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis: A Cohort Study. Issue 7 (July 2016) - Hilhorst, Marc; Arndt, Fabian; Joseph Kemna, Michael; Wieczorek, Stefan; Donner, Yoni; Wilde, Benjamin; Thomas Epplen, Jörg; van Paassen, Pieter; Cohen Tervaert, Jan Willem
Abstract : Objective: The antineutrophil cytoplasmic antibody (ANCA)–associated vasculitides (AAVs) form a group of small‐vessel vasculitides with systemic involvement. Although the etiology of AAVs remains largely unknown, both genetic and environmental factors have been implicated. Recently, certain alleles in the HLA–DPB1 region on chromosome 6 were shown to be associated with proteinase 3 (PR3)–ANCA–positive AAV but not with myeloperoxidase (MPO)–ANCA–positive AAV. The aim of this study was to investigate whether different alleles in the HLA–DPB1 region have clinical and/or prognostic implications in AAV. Methods: One hundred seventy‐four patients with a diagnosis of AAV were recruited at the Maastricht University Medical Centre between 2000 and 2009. Seventeen different HLA–DPB1 alleles were determined using the restriction fragment length polymorphism technique. A validation cohort of 170 AAV patients from the Vasculitis Centre of Luebeck/Bad Bramstedt was included. Results: In the initial cohort, the distribution of HLA–DPB1 alleles was significantly different between PR3‐ANCA–positive compared with MPO‐ANCA–positive AAV patients, ANCA‐negative AAV patients, and healthy controls. Importantly, HLA–DPB1*04:01 was present in 90% of PR3‐ANCA–positive AAV patients compared with 63% of MPO‐ANCA–positive AAV patients, 58% of ANCA‐negative patients, and 63% of healthy controls. Patients homozygous for HLA–DPB1*04:01 had relapses more often compared with heterozygous patients and noncarrier patients. This association persisted after correction for ANCA subtype and diagnosis. In the validation cohort, patients homozygous for HLA–DPB1*04:01 and those heterozygous for HLA–DPB1*04:01 had relapses more often compared with noncarrier patients. When both patient cohorts were merged (n = 344), homozygous patients relapsed most often, followed by heterozygous patients and noncarrier patients. Conclusion: Carriage of HLA–DPB1*04:01 in patients with AAV is significantly associated with an increased risk of relapse compared with HLA–DPB1*04:01–negative patients, irrespective of ANCA status or clinical AAV entity.